LEGAL ANALYSIS OF RESIDENTIAL LAND OWNERSHIP RESTRICTIONS UNDER MINISTERIAL DECREE 6/1998 - Lolita Permanasari; Siti Ngaisah (YURIS: Journal of Court and Justice, 2025)
Concurrent with economic expansion and demographic growth, land scarcity has intensified, necessitating state intervention to maintain equilibrium among competing stakeholders. The Basic Agrarian Law establishes land reform provisions encompassing ownership restructuring and tenure relationships, with Articles 7 and 17 mandating restrictions to prevent land concentration amongst particular groups. Despite legislative requirements that residential land ownership limitations be codified through Government Regulation, such implementing regulation remains absent. Consequently, the State Minister of Agrarian Affairs/Head of the National Land Agency promulgated Decree Number 6 of 1998, restricting residential land ownership to five parcels not exceeding 5,000 square metres cumulatively. This research employs normative juridical methodology with statute approach, examining regulatory hierarchies and enforcement mechanisms. Analysis reveals that whilst Decree 6/1998 constitutes a regulation pursuant to Law 12/2011 Article 100, fundamental deficiencies compromise its efficacy. The Decree lacks prescribed sanctions for violations, contains no supervisory mechanisms, and inadequately addresses ownership restrictions, applying solely to rights elevation rather than rights transfer mechanisms. Furthermore, hierarchical incongruence exists whereby ministerial decree implements primary legislative mandates absent intermediary Government Regulation as constitutionally required. Land office administrative systems lack comprehensive ownership data, rendering declaration verification practically impossible. These findings corroborate previous scholarship documenting weak enforcement mechanisms whilst revealing novel dimensions concerning hierarchical legitimacy and category-specific regulatory dysfunction. The absence of administrative, civil, or criminal sanctions substantially undermines legal enforcement, rendering residential land ownership restrictions ineffective in preventing ownership concentration and achieving equitable distribution objectives.